Intuitionistic fuzzy soft hyperalgebras - Melis Bolat; SERKAN ONAR; Bayram Ali Ersoy (Journal of Hyperstructures)
This study introduces the idea of intuitionistic fuzzy soft hyperalgebra. First, intuitionistic fuzzy soft hyperalgebra isdefined and this definition is supported with an example. A level soft set is formed over a hyperalgebra of an intuitionistic fuzzy soft set. The relation between soft hyperalgebras and intuitionistic fuzzy soft hyperalgebras is given.Finally, intuitionistic fuzzy soft hyperalgebra homomorphism is established and demonstrated if the image and inverse image of an intuitionistic fuzzy soft hyperalgebra are both intuitionistic fuzzy soft hyperalgebras under homomorphism.